Study on improving the radiation efficiency of Sn plasma driven by Laguerre–Gaussian lasers - Huiting Ma; Yun Yuan; Zhiyong Shi; Xinyu Xie; Mengjiao Wang; Wenpeng Wang; Chengyuan Ding; Yuxin Leng; Ruxin Li (AIP Advances)
We present a simulation study on the irradiation of a planar solid tin target using a Laguerre–Gaussian (LG) laser with a wavelength of 2 μm and an intensity of 4 × 1010 W/cm2. Analysis of plasma hydrodynamics revealed that the characteristic hollow intensity profile of the LG laser induced the formation of collisional plasma in the central region. This phenomenon promoted energy transfer from plasma kinetic energy to internal energy, thereby enhancing the conversion efficiency from internal energy to radiation energy. Furthermore, the orbital angular momentum (l = 3) configuration demonstrated optimal radiation efficiency, achieving 3.7%–5.8% compared to conventional Gaussian modes. These results highlight the potential of LG lasers as a promising approach to optimizing extreme ultraviolet source efficiency for future applications.